Faktor-Faktor Pencetus Kekambuhan Asma Pada Anak Di Wilayah Kerja Puskesmas Sibela Kota Surakarta - Safriana, Lina; , Siti Arifah, S.Kp., M.Kes (2017)
Asthma is a chronic disease which occurs in the respiratory tract because there is a hypersensitivity of respiratory tract on the outside stimulants either things, air or activities which cause the respiratory tract inflammated. In Indonesia, asthma is included in the big ten diseases causing pain and death. The highest prevalence rate of asthma from the Riskesdas survey in 2013 reached 4.5%. In Central Java, the asthma sufferers were 113, 023 cases. The Purpose of this research is to know the factors which much trigger the recurrence of asthma in the children. The method in this research is cross sectional through the sampling of total sampling. Samples in this research are as many as 43 mothers who have children of 5-12 years old who are diagnosed as having asthma. The data analysis in this research was conducted in a univariate way that was by seeing the highest percentage amount from the trigger factors of asthma recurrence that was from the frequency table. The results of this research showed that the largest factor with the highest percentage is the weather change that is the cold water, then the factor of food allergies they are instant noodle and snack and the next factor is inhalation allergies such as pet feather and dust. In this research, it was also obtained the children who have the trigger factors of asthma recurrence more than one, they are the food allergies, inhalation allergies and weather change. Conclusion: the weather change that is the cold air in the rainy season is the largest trigger factor of the children' asthma recurrence in Sibela Village of Surakarta Municipity. There are the children who have the trigger factors of asthma recurrence more than one. Keywords: factors which trigger the asthma recurrence, children